A study in Christianity, Marxist ideology and historical engagement with special reference to the liberation theology of José Miguez Bonino - Borman, John (Department of Religious Studies, 2015)
This study examines the seminal thought of a leading Protestant exponent of Latin American liberation theology, Jose Miguez Bonino. It shows that, by a dialectical use of Marxist theory he is able to rediscover a basic and essential Christian understanding of history which requires that Christians be actively engaged in its shaping. Miguez Bonino's choice of the biblical category of the Kingdom of God is examined and is seen to constitute a departure from and an improvement on the conventional model of the Exodus used by most liberation theologians. The Marxist critique of idealism in traditional theology is accepted and serves as a starting point for a revised Christian interpretation of history. The unity of history is traced as originating in the prophetic teaching which linked political happenings with divine sovereignty. The crucial rediscovery of apocalyptic in contemporary European political theology is seen as an important step in the direction taken by Miguez Bonino as is the theological reflection on "thinking in two spheres" by Dietrich Bonhoeffer. The use which Miguez Bonino makes of the concept of the Kingdom of God to emphasize the eschatological significance of human historical action is also outlined. The Marxist emphasis on human responsibility for historical initiative is taken as the point from which to expound an understanding of the Kingdom of God in which the account of the tension between the present age and the future age in apocalyptic is important as is the contrast between continuity and discontinuity in the Pauline concepts of "body", "Resurrection" and "works". Again, Miguez Bonino's indebtedness to Bonhoeffer, this time in his polarity of the ultimate and penultimate is acknowledged. Miguez Bonino's distinctive exposition of the Kingdom as a call to effective action to articulate Christian love is also examined and compared with other models. Political engagement is seen to require mediations in the form of social analysis, theological interpretation and ideology. Sacralization and fanaticism are avoided by the application of ethical criteria and the submission of the mediations to divine judgement. In this regard Miguez Bonino's preference for Marxism is scrutinized and an alternative suggested.